Biomimetic Superstructures Assembled from Au Nanostars and Nanospheres for Efficient Solar Evaporation. (6th March 2019) - Song, Guofen; Yuan, Yang; Liu, Jie; Liu, Qinglei; Zhang, Wang; Fang, Jing; Gu, Jiajun; Ma, Dongling; Zhang, Di
Abstract: The control of the shapes and assembling structures of plasmonic nanoparticles is vital for the optical properties and photothermal conversion performance. Here, gold nanospheres and nanostars are assembled into ridges/disordered nanohole arrays architecture in nanoparticle colloids using light‐trapping Papilio Paris forewings (OPPs) as templates. In solar steam generation, water evaporation efficiency reaches 83.3% for nanostar assemblies (NSAs) and 68.6% for nanosphere assemblies (NSPAs) under 1‐sun (1 kW m −2 ) irradiation. Both the biomimetic superstructures exhibit significant enhancement of near‐infrared light absorption compared to OPPs, and NSAs show higher absorption than NSPAs in the range of 200–2500 nm. Finite element method simulations reveal such broadband absorption is ascribed to the hybridization of localized surface plasmon modes of continuous‐assembled Au nanoparticles in the biomimetic structures as well as the wing photonic structures with light‐transferring ridges with an inverted V shape and light‐trapping disordered nanohole arrays. It is revealed that optical properties of superstructures can be tuned not only by controlling their 3D structures but also by changing the shape of nanosized building blocks. It is hoped that this work will provide inspirations for the design and assembly of nanophotonic structures and devices for solar energy conversion. Abstract : Gold nanospheres and nanostars are assembled into inverted V‐shape ridge/disordered nanohole architectures in colloids using light‐trapping Papilio Paris forewings as templates . They exhibit high efficiency in solar steam generation. It is revealed that optical properties of superstructures can be tuned by changing the shape of nanosized building blocks as well as by controlling their 3D structures.